Loss-of-function mutations of BCOR are an independent marker of adverse outcomes in intensively treated patients with acute myeloid leukemia - Eckardt, Jan-Niklas; Stasik, Sebastian; Kramer, Michael; Röllig, Christoph; Krämer, Alwin; Scholl, Sebastian; Hochhaus, Andreas; Crysandt, Martina; Brümmendorf, Tim H.; Naumann, Ralph; Steffen, Björn; Kunzmann, Volker; et al. (Cancers, 2021)
Acute myeloid leukemia (AML) is characterized by recurrent genetic events. The BCL6 corepressor (BCOR) and its homolog, the BCL6 corepressor-like 1 (BCORL1), have been reported to be rare but recurrent mutations in AML. Previously, smaller studies have reported conflicting results regarding impacts on outcomes. Here, we retrospectively analyzed a large cohort of 1529 patients with newly diagnosed and intensively treated AML. BCOR and BCORL1 mutations were found in 71 (4.6%) and 53 patients (3.5%), respectively. Frequently co-mutated genes were DNTM3A, TET2 and RUNX1. Mutated BCORL1 and loss-of-function mutations of BCOR were significantly more common in the ELN2017 intermediate-risk group. Patients harboring loss-of-function mutations of BCOR had a significantly reduced median event-free survival (HR = 1.464 (95%-Confidence Interval (CI): 1.005-2.134), p = 0.047), relapse-free survival (HR = 1.904 (95%-CI: 1.163-3.117), p = 0.01), and trend for reduced overall survival (HR = 1.495 (95%-CI: 0.990-2.258), p = 0.056) in multivariable analysis. Our study establishes a novel role for loss-of-function mutations of BCOR regarding risk stratification in AML, which may influence treatment allocation.
Gesehen am 18.08.2021